Shock absorber modelling - Skagerstrand, Henrik (My University, 2015)
The automotive industry is becoming increasingly competitive. It is therefore important to keep development time cost down, while still making safe and comfortable cars. One costly part of the development process is the testing done using prototype vehicles, something that can be reduced if more of the testing were done using computer simulations. The shock absorbers of the car play a very important role in the safety and the comfort of the vehicle. Despite this many major car manufacturers use a simple force velocity curve as a computer model of the shock absorber. The engineers at Volvo Car Company has found that there is potential for improvement when it comes to the model of the shock absorber, and Modelon AB was asked to initiate a master’s thesis to develop a physical model of the shock absorber. The model was developed in Dymola, a software based on the language Modelica. The model is a physical representation of the shock absorber with component models representing each of the damper components, such as chambers and valves. Most of the parameters in the model can be taken from physical measurements of the shock absorber, however 10 of the parameters need to be tuned against measurements. The model was verified against tests done on the real shock absorbers in a dynamometer. It was then imported to one of Volvo’s full vehicle models in Adams using FMI, and verified against four poster measurements. In the dynamometer the damper was tested for a frequency range of 0.5 Hz to 30 Hz, and in the four poster a road profile measured by Volvo was used. These tests showed that the model performed significantly better than the force velocity curve, which was the alternative before the thesis work. However due to the simple nature of the force velocity curve based model, it is questionable if the gain of the Dymola model compensates for the extra time required by the engineers to tune the parameters. Therefore the recommendation is to develop the Dymola model further to ensure that the Dymola model is an improvement compared to the force velocity curve, in both model accuracy and amount of tuning work.
Keywords: Transport; Farkostteknik; Transport; Vehicle Engineering